Penguatan Penguasaan Kosakata Bahasa Inggris pada Siswa MTS Terpadu Berkah Melalui Game Pictionary - Tiara Nur Fatimah Almadani; Hesty Widiastuty; Misda Amallia Tuah Aji (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
This study aims to improve English vocabulary mastery among 8A grade students at MTs Terpadu Berkah through the implementation of the Pictionary game method. The research uses a descriptive qualitative approach, focusing on observation and assessment of students’ performance during learning activities. Pictionary, as an interactive learning method, utilizes visual images to help students understand and retain new vocabulary more effectively. The research results show that using Pictionary in English vocabulary learning is effective in enhancing students' understanding and memory of new words. Students actively participated in learning activities, demonstrated high enthusiasm, and showed significant progress in using the vocabulary they learned. Additionally, this approach encourages student collaboration and fosters creativity during the learning process. In conclusion, the Pictionary game can be an effective alternative teaching method for improving vocabulary mastery and learning motivation among students. Implementing this method is expected to provide English teachers with a useful strategy for creating a more engaging and interactive learning environment in the classroom.